Molecular Docking of Secondary Metabolite Compounds of Andrographis Paniculata Plant as Potential Covid-19 Drug Candidate - Netty Ino Ishak; Akram La Kilo; Dandi Saputra Halidi; La Ode Aman; Jafar La Kilo; Weny J.A. Musa (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
The aim of this research was to investigate the interaction between secondary metabolite compounds and the Mpro receptor, which was the main protein in Covid-19. Ligand-receptor interactions were studied using the Molecular Docking method. The validation results indicated that the test ligand Andrographolide had a higher affinity value compared to the standard ligand, with a value of -6.6 kcal/mol compared to the standard ligand's -7.5 kcal/mol. Additionally, the compound 14-Acetyl-3,19-isopropylideneandrographolide, 5,4 dihydroxy-7,8,2',3'-tetramethoxyflavone-5-glucoside had an affinity of -7.5 kcal/mol, Andrographidin A had -7.6 kcal/mol, Andrographiside had -7.7 kcal/mol, Skullcapflavone I had 7.7 kcal/mol, 5-Hydroxy-7,8,2'-trimethoxyflavone-5-glucoside had -7.7 kcal/mol, Apigenin had 7.7 kcal/mol, 5-Hydroxy-7,8-dimethoxyflavone-5-glucoside had -7.8 kcal/mol, Neoandrographolide had -7.8 kcal/mol, Andropanoside had -7.9 kcal/mol, Wogonin-5 glucoside had -8.1 kcal/mol, 5,2',3'-Trihydroxy-7,8-dimethoxyflavone-3'-glucoside had -8.4 kcal/mol, and Bisandrographolide had -8.5 kcal/mol. From the molecular docking results, the secondary metabolite compounds from the Andrographis paniculata plant exhibited significant interactions surpassing the standard ligand N3. Active residue interactions observed included Phe140, Leu141, Asn142, Gly143, His163, Glu166, Gln189, and Thr190. Keywords: Andrographis paniculata; Covid-19 drug; Mpro receptor; molecular docking